2023
DOI: 10.1002/smll.202205968
|View full text |Cite
|
Sign up to set email alerts
|

Trapped Pore Waters in the Open Proton Channel HV1

Abstract: to H V 1 gating. [3] Its structure is homologous to classical voltage-gated channels' voltage-sensing domain (VSD). [4] Experimentally, exclusively closed structures are available -a crystal structure of a chimera between mouse H V 1 and Ciona intestinalis voltage-sensing phosphatase [5] and an NMR structure of the human H V 1. [6] Also, electron paramagnetic resonance (EPR) spectroscopy data decipher the resting structure of H V 1. [7] An AlphaFold structure has been recently added (Figure 1). AlphaFold uses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The proposed closed structure of Geragotelis et al is also too permeable. The same conclusion was reached by looking at the pore dimensions . Perhaps the voltage that was applied in the MD simulation caused a transient opening of the structure, which then did not have enough time to relax.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The proposed closed structure of Geragotelis et al is also too permeable. The same conclusion was reached by looking at the pore dimensions . Perhaps the voltage that was applied in the MD simulation caused a transient opening of the structure, which then did not have enough time to relax.…”
Section: Discussionmentioning
confidence: 65%
“…The same conclusion was reached by looking at the pore dimensions. 53 Perhaps the voltage that was applied in the MD simulation caused a transient opening of the structure, which then did not have enough time to relax. Concerning the open state models, we can safely say that the one R3D model (gerO) is much more easily permeable than the several R2D models we have considered.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple evidence as the high temperature dependence of H V [47,87], the diminished deuterium conductance [83], the H + hopping between pairs of charged residues lining H V pore detected in QM/MM molecular dynamics simulations [152], or more recently the proposed existence of an interrupted water wire within H V 1 pore [153], suggest that a protonable carboxyl group is essential for the selectivity of H V channels. However, the mechanism underlying this selectivity involves also specific physicochemical microenvironments where H + conduction and selectivity are coupled [120,132,141,[154][155][156][157][158].…”
Section: Proton Selectivitymentioning
confidence: 99%
“…pK a values of internal lysine residues in nucleases reported to be as low as 5.3 depending on the polarity of its microenvironment [50]. Studies conducted on proton channels have demonstrated that the arginine residue located at the third position (R3) of the voltagesensing motif (VSM) is exposed to the cytosolic solution when the channel is in its resting state [42,49,[51][52][53][54][55]. Under conditions of negligible pK a changes due to microenvironmental effects of the CgH V 4 structure on K3, our experimental settings permit protonation of the terminal amino group of Lys 150 , which would act as a discrete gating charge [56].…”
Section: Expression and Functional Characterization Of Crassostrea Gi...mentioning
confidence: 99%